IMPROVING THE METHODOLOGY OF SOCIAL-EMOTIONAL DEVELOPMENT OF STUDENTS IN THE PRESCHOOL EDUCATION PROCESS (Global Conference on Multidisciplinary Research and Innovation, 2026)
This thesis theoretically and psychologically analyzes the issues of ensuring the socio-emotional development of children in the preschool educational process and improving the methodology of this process. The study is not based on practical experience but is presented through the analysis of psychological and pedagogical literature. The significance of socio-emotional development in shaping the child’s personality and the improvement of methodological approaches are discussed.
Keywords: Preschool education, socio-emotional development, psychological development, methodology, emotional stability, socialization